Brain-muscle interplay during endurance self-paced exercise in normobaric and hypobaric hypoxia - Rupp, Thomas; Saugy, Jonas J.; Bourdillon, Nicolas; Millet, Grégoire P. (Frontiers in Physiology, 2022)
Purpose: Hypoxia is one major environmental factor, supposed to mediate central motor command as well as afferent feedbacks at rest and during exercise. By using a comparison of normobaric (NH) and hypobaric (HH) hypoxia with the same ambient pressure in oxygen, we examined the potential differences on the cerebrovascular and muscular regulation interplay during a self-paced aerobic exercise. Methods: Sixteen healthy subjects performed three cycling time-trials (250 kJ) in three conditions: HH, NH and normobaric normoxia (NN) after 24h of exposure. Cerebral and muscular oxygenation were assessed by near-infrared spectroscopy, cerebral blood flow by Doppler ultrasound system. Gas exchanges, peripheral oxygen saturation, power output and associated pacing strategies were also continuously assessed. Results: The cerebral oxygen delivery was lower in hypoxia than in NN but decreased similarly in both hypoxic conditions. Overall performance and pacing were significantly more down-regulated in HH versus NH, in conjunction with more impaired systemic (e.g. saturation and cerebral blood flow) and prefrontal cortex oxygenation during exercise. Conclusions: The difference in pacing was likely the consequence of a complex interplay between systemic alterations and cerebral oxygenation observed in HH compared to NH, aiming to maintain an equivalent cerebral oxygen delivery despite higher adaptive cost (lower absolute power output for the same relative exercise intensity) in HH compared to NH.